Relevance of mutual aid and solidarity in measuring authentic leadership: an analysis based on the perceptions of SME employees in Côte d'Ivoire - OUFFOUET , Kouassi François; KOUAKOU , Konan Auguste (Revue Internationale des Sciences de Gestion, 2025)
In Côte d'Ivoire, authoritarian leadership handicaps SMEs' ability to innovate and adapt to market demands. As a result, leaders need to come to terms with the authentic style that fosters employee creativity and adaptability. However, the successful emergence of authentic leadership within our SMEs requires contextualized measurement. To this end, we conducted a qualitative and quantitative study involving 314 SME employees from a variety of sectors. Factor analysis and structural modeling revealed that the relationship of mutual aid and solidarity highlighted by our results is a fifth dimension of authentic leadership of cultural origin that deserves to be taken into account in the Ivorian context.